PENGARUH PENGGUNAAN JENIS ADITIF SEBAGAI SUMBER KARBOHIDRAT TERHADAP KOMPOSISI KIMIA SILASE RUMPUT MULATO - Anas, Moch Rizky; Syahrir, Syahrir (AgriSains, 2017)
This study was aimed to determine the effect of additive typesas chemical composition onchemical composition of Mulato grass silage. The study lasted for 1 month and 3 days, in two phases, 21-days for ensilase process and 12-days for proximate analysis. The experimental design used was a completely randomized design (CRD) consisting of 4 treatments and 5 replications. Such treatment includes: R0 (mulato grass + 0% additives), R1 (mulato grass + 5% rice bran), R2 (mulatoÂ  grass + 5% cassava waste) and R3 (mulato grass + 5% molasses). The parameters measured were the content of dry matter, organic matter, crude protein, crude lipid and crude fiber. Analysis of variance showed that the use of different additives was highly significant (P <0.01) on dry matter content, organic matter, crude protein, crude lipid and crude fiber Mulato grass silage. The addition of additives such as rice bran as much as 5% in the main grass silage made from mulato grass give the best effect to the nutrient content of 27.44% (dry matter), 88.63% (organic matter), 11.20% (crude protein), 3.53% (crude lipid) were highest of all treatments. The conclusion, use of types of additives as carbohydrates source (rice bran, cassava waste and molasses) produced mulato grass silage with better quality compared to control (without additive).Â  Keywords: Mulato grass, silage, Additives, rice bran, cassava waste, molasses.